Management of Julung-Julung (Hemirhampus sp) Fishing Business Using Soma Giop in South Tobelo District, North Halmahera Regency - Hibata, Yubelina; L. Amahorseja, Anggeline (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2021)
The aim of this study was to find out the constraints on the management of julung-julung fishing business in South Tobelo. Specifically, this study will examine fishing businesses that use soma giop method in the fish caught processing, as well as knowing whether this fishing businesses are in an economically viable condition or not. The descriptive method and survey method had been used in this research which resulted the collected data as primary data and secondary data. The data collected had been analyzed using an interactive model starting from data collection, data reduction, data presentation and conclusion. The results of this study indicated that the The management system of soma giop fishing business in South Tobelo consists of preparing fishing units, determining fishing ground, catching processes, selling and marketing, and profit-sharing systems. The highest income of julung-julung julung-julung fishing business in South Tobelo for the year of 2020 for 6 fishing gear was IDR 298.628.333, which was in August. The lowest income was in September, which was IDR. 124.017.500. The results of this study concluded that the fishing business of julung-julung fish with soma giop in South Tobelo is in good condition or economically feasible to continue to be developed. The obstacles faced by fishermen in processing their catch are the lack of counselling and training, and the lack of funds for the business capital.